Ownership, Narrative, Things - Cowan, Dave (Palgrave Socio-Legal Studies, 2018)
This book uses a case study of a low-cost home ownership initiative at the margins of renting and owning provided by social landlords - known as shared ownership - to challenge everyday assumptions held about the 'social' and the 'legal' in property. The authors provide a study of the construction of property ownership, from the creation of this idea through to the present day, and offer a fresh consideration of key issues surrounding property, ownership, and the social. Analysing a diverse range of sources (from archives to micro-blogs, observation of housing providers, and interviews with shared owners), the authors explain the significance of the things (from the formal documents like leases, to odd materials like sweet wrappers and cigarette butts) commonly found in the narratives around shared ownership which are used to construct it as private ownership in everyday life. Ultimately, they uncover how this dream of ownership can become tarnished when people's identities as 'owners' come under threat, and as such, these findings will provide fascinating insight into the intricacies of so-called home ownership for scholars of Law, Criminology, and Sociology.